The Role of Synaesthesia in the Artistic Imagery of Souad al-Sabah - میرقادری, سید فضل الله; خطیبی, علی (LANGUAGE ART, 2019)
Synaesthesia is one of the semiotic categories on which the construction of metaphors is based in the modern poetic imagery. The poet, Souad al-Sabah, could create delightful and influential intonation and significations for her poems in this way since synaesthesia paves the way to express the deep secrets of the poet and it is just the way. An effective poet illustrates such creative and fascinating pictures therewith and invites the audience to think and contemplate beyond the seeming form and to discover the depth of these artistic pictures through it. This study is based on a descriptive-analytic approach which examines the accurate inference of synaesthesia in a poetic imagery through semiotics. The result demonstrates that the poet in her book “Umniah” has used the abstract-sensuous synaesthesia more than the sensuous-sensuous synaesthesia, and the influence of significations of visual synaesthesia, through which the poet makes imagination, is greater than the other types of senses.